EXISTENCIA Y UNICIDAD DE SOLUCIONES REGULARES DE LA ECUACIÓN DE ONDA SEMILINEAL CON DISIPACIÓN LOCALIZADA EN Rn - Perez Salvatierra, Alfonso (2012)
This article is part of the results of the thesis: Asymptotic behavior for semilinear wave equation with local damping in unbounded domains, in this paper we study the existence and uniqueness of smooth solution for the semilinear wave equation with localized dissipation on Rn given by,